Readiness of Educational Institutions in Utilizing Immersive Technology in Learning - Awanis Hidayati; Arie Susanty; Aji Wicaksono; Novaria Nusantara (Southeast Asian Journal on Open and Distance Learning, 2024)
The implementation of technology-enhanced learning in educational institutions is a key indicator of progress and quality. Its successful execution requires a well-established planning process, manifested in the form of readiness measurements. To assess the readiness level for the implementation of e-learning, it is essential to conduct an evaluation of e-learning readiness. This research aims to provide an overview of the general readiness levels of educational institutions collaborating with SEAMOLEC in incorporating immersive technology for learning. The study utilizes the ELR Aydin Tasci model, focusing on four readiness factors: Technology, Human Resources, Innovation, and Self-Development. The findings indicate that two factors, namely technology and self-development, are classified as 'Not Ready' and require minor improvements. On the other hand, human resources and innovation are classified as 'Ready' but also require slight enhancements. The average score obtained, 3.48, reflects a readiness level of 3. In conclusion, the overall readiness of the analyzed educational institutions is categorized as 'Ready' with room for slight improvement.